Republic of Turkey Reform for Competitiveness Technical Assistance : Fostering Open and Efficient Markets through Effective Competition Policies - World Bank (Washington, DC, 2014)
Competition in domestic markets is critical to ensure increased international competitiveness. Firms facing more intense competitive pressures are more likely to introduce new products and upgrade existing product lines. Firms usually acquire many of their inputs (such as transportation, energy, construction, and professional services) in local markets. Competition policies are defined as the set of policies and a law ensuring that competition in the marketplace is not restricted in a way that reduces economic welfare. This report reviews the current status of competition policy in Turkey, focusing on the economy-wide enforcement of competition rules and on specific regulations and government policies that affect product market competition. Economic and legal analysis is used to identify key challenges and to propose specific areas of intervention and reform. In addition, this report provides an evaluation of the potential benefits of pro-competition policies. Turkey is benchmarked against other economies that represent international best practice, as well as regional and global standards, with particular reference to European Union (EU) countries. This study finds that although Turkey has made significant progress in enforcing competition law effectively, it still faces challenges in achieving a comprehensive and coherent policy framework to promote product market competition. The study also finds that there is significant scope to achieve efficiency gains from procompetitive sector policies and more effective economy-wide competition policy enforcement.